PENGARUH ENVIRONMENT, SOCIAL, GOVERNANCE (ESG) DISCLOSURE TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar dalam Indeks Kompas 100 Periode 2020-2022) - Hariyanto, Dani Bagus; Ghozali, Imam (Diponegoro Journal of Accounting, 2024)
Investment is something that is needed by a company in carrying out company operations. ESG disclosure score becomes information as an assessment for investors to make investment decisions. This study aims to examine the effect of environment, social, governance (ESG) disclosure on firm value. The independent variables used in this study are environment disclosure score, social disclosure score, and governance disclosure score. Meanwhile, the dependent variable in this study is firm value.The population used in this study are companies listed in the KOMPAS 100 Index. This research was conducted using purposive sampling method, with 150 samples used which are companies that publish annual reports and publish ESG disclosures in the period 2020-2022. Multiple linear regression analysis using the SPSS For Windows Version 26.0 application in this study to test environmental, social, governance (ESG) disclosure on firm value.The results of this study indicate that social disclosure score has a positive and significant effect on firm value. Meanwhile, environment disclosure score and governance disclosure score have no effect on firm value. Thus, the results of the study can expand the literature regarding ESG disclosure on firm value in companies in developing countries. This provides insight to stakeholders in identifying the role of ESG disclosure in companies in Indonesia.